(untitled) (Revista Electrónica REDINE, 2018)
This article aims to develop a strategy for teaching practice of physics at the basic training of students of the Dean of Civil Engineering (DIC), and also evaluate the processes of meaningful learning of ideas and concepts formulated by Ausubel, as well with the help of a guide students will have the opportunity to mount practices and to exercise the observation of the physical phenomenon, justify and explain it from established theories, using technology. The research is framed within the modality of feasible project being located within the qualitative paradigm, supported by the literature and document review. The module includes as main tool the Data Studio program, which allows obtaining and displaying data through the sensor and the computer as a resource using a spreadsheet and various tools provided by the package. It is expected these results that students approach the work of the professional, to make decisions in experimental arrangements, estimating possible outcomes, describing the essence of physical phenomena through simple graphics, contrasting the theoretical model and experimental work in the form collaboratively with other students and teachers.